The distance between two points (x1, y1) and (x2, y2) is given by sqrt[(x2 - x1)^2 + (y2 - y1)^2]

For the points (2, 3) and (0, 6), the distance between them is:

sqrt[(2 - 0)^2 + (6 - 3)^2]

=> sqrt[4 + 9]

=> sqrt 13

**The required distance between the points is sqrt 13**

The formula for distance between points with coordinates (x, y) and (X, Y) is `D = sqrt((X - x)^2 + (Y - y)^2)`

To determine the distance between (2, 3) and (0, 6), x = 2, X = 0, y = 3 and Y = 6.

Substituting these values in the formula gives the distance as:

D = `sqrt((0 - 2)^2 + (6 - 3)^2)`

= `sqrt(4 + 9)`

= `sqrt 13`

The distance between the points (2, 3) and (0, 6) is `sqrt 13`

The distance between 2 points is the lengths of the segment that joins the 2 points.

We'll note the points: (2, 3) and (0, 6)

We'll write the formula of the distance:

[AB] = sqrt[(x2-x1)^2 + (y2-y1)^2]

We'll substitute the coordinates into the formula:

[AB] = sqrt[(0-2)^2 + (6-3)^2]

[AB] = sqrt (4 + 9)

[AB] = sqrt 13 units

The distance between the given points A(2, 3) and B(0, 6) is sqrt 13 units.